Water Quality Profile of Sg. Langat - Suki, Anhar; Yusoff, Mohd. Kamil; Mok, Thean Poe (1988)
This study was conducted between August and December 1985 in order to assess polluting effects from different landuse patterns. Nine sampling sites were chosen over a distance of 60 km. A number of physical and chemical parameters were analysed. Statistical tests and Water Quality Index were used to evaluate the water quality variation. The result shows that relatively high BOD, suspended solids, electrical conductivity and turbidity occurred after Hulu Langat town. The statistical test indicated that the water quality variation is significantly different (p < 0.05); the Water Quality Index shows that the water quality near Kajang town has deteriorated compared to other stations.